Sister Spider Knows All - Adrian Fogelin (U.S.A, 2003)
Twelve-year-old Rox and her grandmother Mimi sell at a flea market every weekend to supplement the family's only income, that of construction worker and college student, cousin John Martin.
Keywords: Friendship - Relationship